A Study Protocol on Effect of Postural Deviation on Functional Capacity in Patients with Chronic Respiratory Disease - Ruchita Rao Chilkapurwar; Vaishnavi Yadav (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: According to WHO Chronic respiratory diseases are diseases of the airways and lung.Chronic obstructive pulmonary disease , asthma, occupational lung diseases and pulmonary hypertensionare among the most severe. Chronic respiratory disease is generally divided among adults into obstructiveand restrictive conditions. Restrictive lung disorders are characterized by decreased volumes of the lung,either due to a lung parenchyma change or due to pleura, chest wall or neuromuscular apparatus disease.Unlike obstructive lung diseases such as asthma and chronic obstructive pulmonary disease, which exhibitnormal or elevated total lung capacity (TLC), restrictive diseases are correlated with a reduced (TLC). Thesepresenting symptoms of chronic respiratory disease results in the postural deviations. It mainly affect thecervical and lumbar region of the spine which include forward head posture, upper thoracic kyphosis whichoccurs due to continues use of accessory muscles of breathing.The functional capacity of the patients areassessed by performing the 6-minute walk test (6MWT) it is fairly easy for evaluating the status of cardiacand pulmonary diseases.Methoud/Design: The study is designed as observational and correlation study. The participants will beselected as per inclusion and exclusion criteria from AVBRH , sawangi Meghe for the study. The durationof the study will be 6 months. Study include evaluation of the posture with the help of kinect azure andevaluation of functional capacity using 6 MWT. Correlation of 6MWT,Vo2 peak with severity of the posturaldeviation.Discussion: This study details about effect of postural deviation on functional capacity in patients withchronic respiratory disease. Many studies have been done on assessment of the postural deviation in COPDpatients but there is scarcity of literature which focus on the other respiratory conditions also. Kinect azure isthe objective measure for assessment and gives the detail evaluation of posture. Since deviated posture putsextra load on musculoskeletal system which indirectly affects the functional capacity. So the this study aimsto observe degree of postural deviation and relate it to the functional capacity. The present study can provideus the baseline idea data about the importance of maintaining good posture in chronic respiratory diseasespatients for improving functional capacity and also importance of good postural habit in exercise program.